After more than half a century: Dielis diabo (Hymenoptera: Scoliidae: Scoliinae), a new scoliid from the Neotropics - Golfetti, Ivan Fernandes; Noll, Fernando Barbosa (Zootaxa, 2023)
A new species of Scoliidae, Dielis diabo n. sp., is described from material previously collected and misidentified as Dielis dorsata Fabricius, 1787 after almost 60 years since the last description of a neotropical scoliid. Detailed morphological descriptions of the female and male are presented, as well as differences between the new species and Dielis dorsata.